Aquifer analysis with seismic methods in Parambahan Region - Arbi, Yaumal; Arifin, Ari Syaiful Rahman; Yandra, Muvi (Jurnal Pendidikan Teknologi Kejuruan, 2021)
The problem faced by farmers in Parambahan Region during the dry season is agricultural land does not get adequate water supply from existing irrigation channels, as a result, farmers can only carry out agricultural activities during the rainy season in Parambahan Region Lima Kaum Subdistrict, district of Tanah Datar. This study aims to determine the location and depth of soil layers containing groundwater by using the seismic method, measurements are carried out at two points, with the length of the track at the first point being 80 meters, and at the second point 70 meters, each measurement on seismic data collection using 4 geophones as signal capture sensors, with a distance between geophones of 5 meters. The results of this study that the wave velocity at the first data point collection was 169.49 m/s and the lowest was 87.1 m / s, and the wave velocity at the second point was 129.68 m / s and the lowest was 48.07 m / s. from the wave velocity, it can be seen the type and depth of the groundwater layer at the point of data collection on the first pass, which is a depth of up to 27.5 meters of the possibility of soft soil and a depth of about 30 to 40 meters of watery soft soil at that depth may have groundwater, and at that point, the second passage at a depth of up to 25 meters is likely to be soft soil and at a depth of around 25 to 35 meters of watery soft soil at that depth, there is groundwater.